PENGARUH KOMPETENSI DAN PROMOSI JABATAN TERHADAP KINERJA KARYAWAN PT POS INDONESIA WILAYAH SINTANG - admin, RENI WIDAYANTI B1021131070 (Jurnal Manajemen Update, 2017)
The purpose of this research is find out the influence of competency and promotion to the performance of PT Pos Indonesia Sintang’s employees. The data used is primary data (from questionnaires) and the samples was 52 people. The multiple linear regressions is used as the analysis technique and hypothesis testing used t test and f test as well as the coefficient of determination. The analytical method used is multiple linear regression analysis using SPSS v.20.0. The results of data analysis showed that the competency and promotion partially positive and significant impact on employee performance of PT Pos Indonesia Sintang’s. The higher level of the competency that the employee has, the better and optimal performance can also be produced. Similarly with the promotion, the better and higher promotion which is received by the employee, the more optimal performance will be generated. Keywords: Competency, promotion, and Employees’ Performance.